Speech act performance : - Bax, Stephen (ohn Benjamins Pub. Company, 2010)
Speech acts are an important and integral part of day-to-day life in all languages. In language acquisition, the need to teach speech acts in a target language has been demonstrated in studies conducted in the field of interlanguage pragmatics which indicate that the performance of speech acts may differ considerably from culture to culture, thus creating communication difficulties in cross-cultural encounters